2022
DOI: 10.3390/e24030366
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Approach to Predict Football Matches with Changed Home Advantage in Spectator-Free Matches after the COVID-19 Break

Abstract: Since the coronavirus disease 2019 (COVID-19) pandemic, most professional sports events have been held without spectators. It is generally believed that home teams deprived of enthusiastic support from their home fans experience reduced benefits of playing on their home fields, thus becoming less likely to win. This study attempts to confirm if this belief is true in four major European football leagues through statistical analysis. This study proposes a Bayesian hierarchical Poisson model to estimate paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the major European competitions (i.e., Ligue 1, Serie A, LaLiga, the Premier League, and Bundesliga) during the 2019/2020 season, with fans in the stadia (before the restrictions), home teams scored more goals than visitors [7], because the number of dangerous attacks was higher. In contrast, another study [14] comparing the pre-COVID-19 and COVID-19 period in European soccer matches showed a decrease in the goals scored by home teams in ghost matches, which also affected the points and ranking. Another indicator that was affected during the COVID-19 period, in similar studies [9,12,13], was the higher number of fouls committed by home teams which, in turn, resulted in more yellow cards.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the major European competitions (i.e., Ligue 1, Serie A, LaLiga, the Premier League, and Bundesliga) during the 2019/2020 season, with fans in the stadia (before the restrictions), home teams scored more goals than visitors [7], because the number of dangerous attacks was higher. In contrast, another study [14] comparing the pre-COVID-19 and COVID-19 period in European soccer matches showed a decrease in the goals scored by home teams in ghost matches, which also affected the points and ranking. Another indicator that was affected during the COVID-19 period, in similar studies [9,12,13], was the higher number of fouls committed by home teams which, in turn, resulted in more yellow cards.…”
Section: Discussionmentioning
confidence: 87%
“…The following data (game indicators) were collected for each team and match played: (1) yellow cards, (2) red cards, (3) ball possession, (4) total shots, (5) shots on goal, (6) shots off goal, (7) free kicks, (8) corners, (9) offsides, (10) goalkeeper saves, (11) fouls committed, (12) attacks, (13) dangerous attacks, (14) total passes, and (15) tackles. These were the dependent variables.…”
Section: Sample and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, research topics emerged that could be approached in the unique context of the COVID-19 pandemic. For example, the scholarly soccer literature explored whether there was still a significant home-advantage effect in soccer matches played away from home during the pandemic ( McCarrick et al, 2021 ; Lee et al, 2022 ). Through this topic, future research directions can be anticipated as areas where comparative approaches can be made considering the current post-COVID-19 situation.…”
Section: Discussionmentioning
confidence: 99%
“…Using topic modeling to study research trends can provide useful information along with new ideas for future research ( Lee et al, 2021 , 2022 ). These results can be used to form a body of knowledge by quantitatively analyzing a large number of papers and qualitatively interpreting the discovered knowledge structure to find certain patterns in scattered data ( Miyata et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%